The Effect of Black Cumin Seed Oil on Active Smokers Based on Interleukin-1β Activity and Neutrophil - Shabrina Arwi Laily; Titiek Hidayati; Akrom Akrom; Vivi Sofia (Pharmacy Faculty, Universitas Muhammadiyah Purwokerto, 2021)
Health problems due to exposure to cigarettes cause the body to fight against the occurrence of immune responses, one of which is leukocytes. The most common types of leukocytes are neutrophils, which are about 50-70% with a function as the body's line of defense against foreign substances. One of the toxic components in cigarettes is nicotine. Nicotine in cigarettes can induce the production of IL-1β. Black Cumin Seed Oil (BCSO) in various studies has been widely used as a supplement, especially as an immunomodulator. This study used a single-blind Randomized Controlled Trial (RCT) method, with a total of 39 test subjects divided into four groups for 30 days. Group 1 received placebo 3x1 capsules/day, group 2 received BCSO 3x1 capsules/day, group 3 received BCSO 3x2 capsules/day, and group 4 received BCSO 3x3 capsules/day. Data analysis used a one-way ANOVA test to see the average neutrophils between treatment groups. While the average levels of IL-1β using the method of Kruskall Wallis. The test results are said to be significant if p 0.05. The p value of the ANOVA test was 0.16 neutrophil levels. In Kruskal Wallis, the –p value for IL-1β is 0.43. BCSO administration does not affect IL-1β levels in smokers and BCSO doses 3x1 capsules/day can reduce neutrophil levels.